The effect of the curriculum on the way of play in the development of motor appreciation and some motor abilities of kindergarten children - Jawad Kadhim Almayah, Sanaa (International Journal of Psychosocial Rehabilitation, 2020)
The effect of the curriculum on the way of play in the development of motor appreciation and some motor abilities of kindergarten children. Kinetic abilities have a great role in raising children towards a better future, because the child’s entry into kindergarten leads him to a new environment that tries to discover and form his experiences and information, and anifested the problem of research in the identification of the impact of a proposed curriculum in a way to play in the development of motor appreciation and some motor abilities of kindergarten. The first section contains the introduction and dealt with the stage of kindergartens, which must be prepared in a meaningful manner according to educational foundations and educational goals that work to form the personal aspects of the child and build. They also discussed the process of education at this stage and the development of multiple plans and strategies that work to raise the tendencies of children and the development of freedom of thought and curiosity and exploration and that most of these things are done through play. The importance of research in the preparation of a method of play works to give children the kinetic abilities and cognitive awareness and then achieve a level of motor appreciation and through purposeful, diverse and exciting games contribute to the best use of their senses in the performance of movements that serve their integrated development to be more willing to move to the next stage of studying. The problem of research is that the curriculum prepared for kindergartens does not focus on the development of their knowledge and development so that they can discover their physical and mental abilities to benefit in the formation of interdependent movements, and enables children to use more than one member to accomplish movements by linking cognitive and motor information to obtain targeted and targeted motor behavior And true.